The Italian resistance : fascists, guerrillas and the Allies - Behan, Tom, 1957- (Pluto Press ; Distributed in the United States of America exclusively by Palgrave Macmillan, 2009)
One of the enduring myths about World War Two is that only the Allies liberated occupied Europe. Many countries had anti-fascist Resistance movements, and Italy's was one of the biggest and most politically radical yet it remains relatively unknown outside of its own homeland. Within Italy many plaques and streets commemorate the actions of the partisans - a movement from below that grew as Mussolini's dictatorship unravelled. Led by radical left forces, the Resistance trod a thin line between fighting their enemies at home and maintaining an uneasy working relationship with the Allies. Essential for courses on World War Two and European history, Tom Behan uses unpublished archival material and interviews with surviving partisans to tell an inspiring story of liberation.